Diabetes Mellitus Type-1 and Psychosocial Intervention to Improve Quality of Life - Sarah Amalia (Open Access Indonesian Journal of Medical Reviews, 2021)
Systemic abnormalities of type-1 diabetes mellitus cause impaired glucose metabolism characterized by chronic hyperglycemia. This literature review aimed to describe the psychosocial intervention in type-1 diabetes mellitus. Responsibility for the care of children with diabetes implies the impact of a psychosocial dimension on children and their families. This chronic disease affects different stages of the life of the people who suffer from it. Adolescence is considered to be one of the most complicated stages due to all the changes that are experienced, both physiological and psychosocial, with young people with diabetes being susceptible to higher levels of stress and psychological illness. In addition, stress management and training in coping skills have reduced diabetes-related stress and increased adolescent social interaction. In conclusion, family relationships, better knowledge and understanding, greater self-confidence, and greater motivation encourage patients with T1DM to control their diabetes.